Microfluidics for the rapid detection of Escherichia coli O157:H7 using antibody-coated microspheres. Issue 1 (1st January 2021) - Song, Bo; Yu, Jiayuan; Sun, Yan; Wang, Qiao; Xu, Shengnan; Jia, Yichen; Lin, Shuying; Zhang, Yueying; Wang, Chen; Zhang, Yingbo; Zhang, Xiaojie
ABSTRACT: This study developed a novel method for the rapid detection of Escherichia coli ( E. coli ) O157:H7 on a microfluidic platform. First, the concentration of bacteria in a sample was determined with the adenosine triphosphate (ATP) method. Then, the specific detection of E. coli was achieved in a microfluidic chip by the immune-microsphere technique. The influences of the culture time, flow rate and capture time on the detection of the target bacteria were investigated systematically. Generally, with increasing capture time, more bacteria could be captured by the microspheres, which had a positive effect on bacterial detection. Furthermore, the sensitivity and specificity of the method were also tested. The results showed that this method could specifically detect E. coli with a sensitivity as high as 49.1 cfu/μL; the consumption of bacteria was 1 μL, and the reagent was at the microliter level. The testing time can be controlled within one and a half hours, and the cost of testing was approximately RMB 10. The method described in this article is simple and accurate and has great application value in bacterial detection for medical diagnostics.